Lygtys ir nelygybės su parametru - Sokolovas, Sergejus; Sokolovaitė, Eglė (Lietuvos matematikos rinkinys, 2021)
In this paper there are clarified a few principal concepts that are then being used to explain the process of solving and analysing equations and inequalities with parameter. The process of analysing inequalities is conveyed by including a method of areas which means the intervalmethod expanded to the plane.